2018
DOI: 10.1021/acsami.7b14888
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Eluting Electrospun Nanofiber Yarns for Antithrombotic Vascular Sutures

Abstract: The surgical connection of blood vessels, anastomosis, is a critical procedure in many reparative, transplantation, and reconstructive surgical procedures. However, effective restoration of circulation is complicated by pathological clotting (thrombosis) or progressive occlusion due to excess cell proliferation that often leads to additional surgeries and increases morbidity and mortality risk for patients. Pharmaceutical agents have been tested to prevent these complications, but many have unacceptable system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 53 publications
(82 reference statements)
2
21
0
Order By: Relevance
“…Tensile strength of the three‐layer yarn was about 3.7 cN.tex −1 , which was like Sohanaki's [ 8 ] three‐layer yarn and more than the nanofibrous yarn in the work of Jin et al [ 18 ] and Bae et al, [ 36 ] which was reported 2.2 cN.tex −1 and 2.6 N.tex −1 , respectively.…”
Section: Resultssupporting
confidence: 63%
“…Tensile strength of the three‐layer yarn was about 3.7 cN.tex −1 , which was like Sohanaki's [ 8 ] three‐layer yarn and more than the nanofibrous yarn in the work of Jin et al [ 18 ] and Bae et al, [ 36 ] which was reported 2.2 cN.tex −1 and 2.6 N.tex −1 , respectively.…”
Section: Resultssupporting
confidence: 63%
“…S. Bae et al observed the tested release of heparin from PLGA/PEO yarns. It was possible to adjust the release rate through electrostatic interactions, and the best was 65% at 20 days of incubation [ 26 ]. In our studies, we obtained the layered scaffolds with long-term heparin release thanks to the introduction of heparin directly into the electrospun fibers and by their combination with a porous PCL layer.…”
Section: Resultsmentioning
confidence: 99%
“…An electrospun material with high gel fraction, good tensile strength, and impressive shape recovery may be useful in medical procedures such as vascular, tendon, or bone repair. Application of electrospun materials in vascular grafts and repair has been a popular area of research [25,[41][42][43][44]; however, none have incorporated the shape memory effect, which could improve sleeve fitting and reduce tension at the healing site for anastomosis applications. These studies will help direct future studies into the biomedical uses of this material.…”
Section: Discussionmentioning
confidence: 99%